Teachers’ Perspectives on Internet Use: Towards the Digital Inclusion of Students with Intellectual Disability or Autism Spectrum Disorder - Esther Chiner; Marcos Gómez-Puerta; Consuelo Manosalba; Miguel Friz-Carrillo (Disabilities)
People with disabilities have difficulties in digital inclusion, although it is considered essential for participation in the knowledge-based society. This form of inclusion seeks to ensure equal opportunities in the use of digital technologies and their active participation as citizens in the virtual world. The educational environment is key to this digital inclusion, but teacher attitudes and training influence its effectiveness. The aim of this study was to explore, through a descriptive cross-sectional study, Chilean teachers’ perspectives on the safety, benefits, and risks of the Internet for students with intellectual disabilities or autism spectrum disorder. A questionnaire was administered to 211 pre-service and in-service teachers. The results highlight the perception of the Internet as an unsafe environment for these students, where risks prevail over potential benefits. These findings underline the need to improve both initial and ongoing teacher training in digital skills and risk mediation for these students in order to ensure the digital participation of all students.